Buyers’ Perception of the Marketing Mix of Luxury High Rise Residence (LHR) in Kuala Lumpur’s Golden Triangle (KLGT) - Chuon, Amy; Hamzah, Hasniyati (International Journal of Property Sciences (E-ISSN: 2229-8568), 2019)
In Malaysia, luxury high-rise residence (LHR) is a residential sub-sector that is popular among developers due to its perceived high profit margin, especially for limited development land in the city centre. In a housing market characterised by substantial overhang in the luxury segment, an examination of the marketing mix of LHR is timely to enable informed decision by developers. Using Kuala Lumpur’s Golden Triangle (KLGT) as the study area, this study examines buyers’ perception of the 4Ps of marketing - Product, Price, Place and Promotion – of LHR in KLGT. Based on a quantitative approach, a questionnaire survey was conducted on 180 respondents comprising existing LHR owners in KLGT. We found that because the majority of the respondents purchased LHR for investment and own stay purposes, the property elements of LHR were deemed more important than its luxury elements, as reflected in the ranking of the 4Ps attributes. Place was ranked as the most important marketing factor by the respondents, followed by Price, Product and Promotion. This study improves understanding of the 4Ps of marketing for LHR in KLGT whereby property developers should place more weightage on the location and neighbourhood of the LHR rather than relying on pricing and promotional strategies.